Returns to Education in Greece: Evidence from the 1977 Labor Market Survey using the Greek Civil War as an Instrument - Harry Anthony Patrinos (Global Labor Organization (GLO), 2022)
Greece experienced a devastating civil war in 1946-1949. This led to many deaths, economic losses, and severe reductions in schooling expenditures and attendance. Using an instrumental variables approach, we estimate the 1977 returns to schooling, showing that for those affected by the civil war, the returns to schooling are higher than the corresponding least squares estimate.
Keywords: I21; J31; 330; Returns to education; instrumental variables; civil war; Greece